Faktor-faktor yang Berhubungan dengan Kejadian Stunting pada Bayi Usia 24-35 Bulan - Kristiova Masnita Saragih; Vina Dwi Wahyunita (Universitas Faletehan, 2024)
Stunting can be caused by risk factors and pregnancy complications. Both in national and global context, it can disrupt the productivity and quality of human resources in the future. Examining the correlation of factors related to stunting in infants aged 24-35 months is the purpose of this study. This study used a cross-sectional design based on observational analytics. The participants were mothers living around the Saumlaki Public Health Center who gave birth to toddlers. The total samples were 70 mothers with the following variables: age, gestational age, maternal nutritional status, income, education, and knowledge. The Chi-Square test was used to analyze the data of this study. The data collection techniques included surveys and careful observation. This study found that the incidence of stunting in toddlers aged 24-35 months was correlated with factors such as maternal age <20 years (p 0.001), history of gestational age between 20-36 weeks (p <0.001), low education level (p <0.001), low-income level (p <0.001), lack of knowledge (p <0.001), and maternal nutritional status (p <0.001). Health workers need to provide health education about the dangers of stunting-risky pregnancy, such as early pregnancy, premature pregnancy and mothers who experience KEK.